Agricultural Land Suitability Analysis for Land Use Planning: The Case of the Madrid Region - Nerea Morán-Alonso; Andrés Viedma-Guiard; Marian Simón-Rojo; Rafael Córdoba-Hernández (Land)
Agricultural land is a key resource for territorial resilience. In the European context, fertile soils are under pressure not only from urbanisation processes, abandonment and the establishment of non-agricultural uses but also from agriculture that is not well adapted to territorial resources. In order to inform urban planning, a methodology is proposed and applied to the Madrid region to analyse the suitability of agricultural land uses with respect to agrological quality. The majority of agricultural uses in the region are well adapted to the agroecological quality of the land; larger areas of over-exploited land are located along some of the region’s rivers and in the Campiña, while under-utilised land is mainly found in the south-west and in the metropolitan comarcas. This methodology is based on official and open-access information, so it can be easily replicated and used to inform land planning. We propose three strategies depending on the suitability of land use: the introduction of crops in priority areas for horticulture or arable crops, agricultural protection areas and ecological regeneration areas.